Long working distance high resolution reflective sample imaging via structured embedded speckle illumination - Haridas, Aswin (2020)
Imaging beyond the diffraction limit at longer working distances using enhanced microscopic configurations has always been a challenge for biological and engineering samples. Even though multiple techniques have been widely used for sub-diffraction limit resolution imaging, the achievable resolution was relying on the use of objective lenses with a high numerical aperture (NA). In the case of engineering samples, in addition to sustaining higher resolutions at large working distances, improving the signal-to-noise ratio (SNR) is also critical. In this context, we propose and demonstrate a concept for high-resolution imaging at large working distances, termed as structured illumination embedded speckle microscopy. An imaging resolution of ~ 310 ± 5 nm was achieved with a microscope objective (0.55 NA; 50X) having 11 mm long working distance using a Siemen's star as the test sample. The demonstrated microscopy is therefore envisaged for engineering applications that demands high-resolution, high SNR imaging at long working distances.